Outline for an etiology of crime - Eugenio Raúl Zaffaroni (2021)
The authors explain the current etiology of crime based on the latent or real functionality of the punitive power that reproduces crime and a large incarceration with the financialization of the economy. In the same vein, they highlight the idea that crime plays a positive role for the transnational corporate finance power and its local agents. This denies all the alleged manifested functions (prevention, reintegration, containment, etc.) and also the one of the common media discourse of the war metaphor (war on crime), because as the authors declare: What is encouraged to be reproduced cannot prevented, nor there can be a war where someone trains the enemy's soldiers.